The European Database of Terrorist Offenders (EDT): development, Usability and Options - Alberda, Daphne (Perspectives on terrorism, 2021)
The European Database of Terrorist offenders (EDT) is based on comprehensive judicial information of convicted or deceased terrorist offenders, including social, psychological and psychiatric reports. This new empirical database is the result of a European cross-border collaboration between judicial organizations and scientists within the European Union. The EDT dataset comprises developmental, individual, biographical and contextual factors, which are potentially related to engagement in violent extremism and terrorism. It supports research seeking to identify critical risk and protective factors for violent extremism and terrorism. The EDT dataset could be used to conduct studies aimed at the identification of significant personal and contextual risk and protective factors for terrorism and violent extremism, improving and validating risk assessments, as well as identifying pathways into terrorism and radicalization. Moreover, this data can assist in the design of effective policy, prevention and intervention practices regarding potential violent extremist and terrorist offenders in Europe and elsewhere. The aim of this article is twofold: firstly, it seeks to present the EDT, along with discussing its development and methodology. To this end, the inclusion criteria and coding principles are discussed, alongside quality-, privacy- and security issues associated with the gathering and processing of judicial data, together with some preliminary statistics. Secondly, it aims to discuss potentials for research based on EDT data. Accordingly, potential applications and future developments of the EDT are discussed as well as urgent needs to use and further develop this comprehensive and unique database.